Detection and Characterization of Low Probability of Intercept Triangular Modulated Frequency Modulated Continuous Wave Radar Signals in Low SNR Environments Using the Scalogram and the Reassigned Scalogram (Global Journals of Research in Engineering, 2024)
Digital intercept receivers are currently moving away from Fourier-based analysis and towards classical time-frequency analysis techniques for the purpose of analyzing low probability of intercept radar signals This paper presents the novel approach of characterizing low probability of intercept frequency modulated continuous wave radar signals through utilization and direct comparison of the Scalogram versus the Reassigned Scalogram Triangular modulated frequency modulated continuous wave signals were analyzed The following metrics were used for evaluation percent error of carrier frequency modulation bandwidth modulation period and chirp rate Also used were percent detection lowest signal-to-noise ratio for signal detection and time-frequency localization x and y direction Experimental results demonstrate that overall the Reassigned Scalogram produced more accurate characterization metrics than the Scalogram